Atlas of pain management injection techniques - Waldman, Steven D; Shavell, Lauren; Carrico, Patrick (Saunders/Elsevier, 2007)
This resource conveniently places at your fingertips every essential pain management injection technique used today - in a straightforward, beautifully illustrated manner that lends itself to ready implementation in any clinical setting. Leading expert Steven D. Waldman, MD, JD gives you the benefit of his extensive experience, both as a clinician and as the author of numerous best-selling pain management references. From head and neck to foot and ankle - and everywhere between - this reference equips you to perform a complete range of clinical injection techniques with greater confidence!See exactly how to proceed and fully understand the nuances of each technique thanks to hundreds of illustrations - many in full color, and many new to this edition - demonstrating relevant anatomy, insertion sites, and more.Perform each technique like an expert and avoid complications with clinical pearls in each chapter.Obtain proper reimbursement with Physician\'s Current Procedural Terminology-2006 (CPTTM) coding information for each procedure.Keep current with updated coverage encompassing the latest identification and definition of pain syndromes.Gain access to all images in the book with accompanying CD-ROM.
Keywords: farmacie a farmakologie; patologie; bolest; Pain; injekce; Injections; Injections, Intra-Articular; injekce intraartikulární